Evaluation of Haematological Parameters in Dengue Patients - Sushil Kumar Sharma; Mansi Rathore (Asian Journal of Medical Research, 2022)
Background: The aim is to evaluate haematological parameters in dengue patients. Subjects and Methods:   Thirty patients in age ranged      2 months- 83 years of either gender of dengue infection were enrolled in the study. Haematological investigation such as haemoglobin (Hb), red blood cell count (RBC), platelet count, packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular haemoglobin concentration (MCHC), red cell distribution width (RDW- CV), total leucocyte count (TLC), mean platelet volume (MPV) etc. was measured in all. Results: Haemoglobin level <8 g/dl was seen among 4 (13.4%) and >8 g/dl in 86.7%. The mean haemoglobin level was 10.25 g/dl). Mean platelet volume found to be 9.53 fL. There were 11 (36.7%) patients with MPV >9 fL and 19 (63.3%) with MPV <9 fL. Mean corpuscular haemoglobin concentration found to be 33.4 g/dl. There were 29 (96.7%) patients with MCHC > >30 g/dl and 1 (3.3%) with MCHC <30 g/dl. Mean red cell distribution width found to be 15.9%. There were 12 (40%) patients with RDW- CV > 16% and 18 (60%) with RDW- CV <16%. Red blood cell count found to be 4.1 million cells/mcL, PCV was 43.8%, MCV was 85.9 fL, MCH was 30.8 pg, TLC was 11.7 x 109 cells per litre, neutrophils was 79.5 x 109 cells per litre, lymphocytes was 30.7 x 109 cells per litre, monocytes was 5.54 x 109 cells per litre, basophils was 0.06 x 109 cells per litre and eosinophils was 3.09 x 109 cells per litre. Conclusion: Dengue infection is spreading worldwide. Haematological parameters such as packed cell volume, mean corpuscular volume, mean corpuscular haemoglobin concentration, red cell distribution width helps in identification and early management of dengue cases.